2014
DOI: 10.1103/physrevd.90.084032
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing repulsive gravity with curvature eigenvalues

Abstract: Repulsive gravity has been investigated in several scenarios near compact objects by using different intuitive approaches. Here, we propose an invariant method to characterize regions of repulsive gravity, associated to black holes and naked singularities. Our method is based upon the behavior of the curvature tensor eigenvalues, and leads to an invariant definition of a repulsion radius. The repulsion radius determines a physical region, which can be interpreted as a repulsion sphere, where the effects due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…For further recent studies of the δ-metric, see [37][38][39][40][41][42] and the references cited therein.…”
Section: Gravitational Shift Of Frequency In δ-Spacetimementioning
confidence: 99%
“…For further recent studies of the δ-metric, see [37][38][39][40][41][42] and the references cited therein.…”
Section: Gravitational Shift Of Frequency In δ-Spacetimementioning
confidence: 99%
“…The ability to neglect all densities except matter and dark energy comes from the fact that we focus only on the late time universe. In such a picture, cosmography works well in the regime where H 0 a 0 /c ≫ 1, which represents the condition for obtaining an accelerated expansion today 6 , with a(t 0 ) = a 0 . In this picture, the expansion of the pressure in terms of ρ is a first example of a cosmographic series.…”
Section: The Path To Cosmography: Basic Requirements and Strategiesmentioning
confidence: 99%
“…Indications of repulsive effects in gravity are not new, specially in the case of naked singularities [4]. Several intuitive approaches have been proposed to understand repulsive gravity, but only recently an invariant definition in terms of geometric objects was formulated [6]. Indeed, it was shown that the behavior of the curvature tensor eigenvalues can be used to find the places where repulsive gravity appears.…”
mentioning
confidence: 99%
“…Repulsive effects in a homogeneous and isotropic universe Although there are several intuitive ways to define repulsive gravity, only recently an invariant definition in terms of the curvature tensor eigenvalues was formulated which gives physically reasonable results in the case of all naked singularities investigated so far [6]. The idea is that the curvature tensor eigenvalues contain in an invariant manner all the information about the behavior of gravity.…”
mentioning
confidence: 99%
See 1 more Smart Citation